What lo que es comes to be considered: Pragmatic functions and Sociolinguistic Variation - Montoro del Arco, Esteban T. (Círculo de Lingüística Aplicada a la Comunicación, 2022)
As a discourse marker, lo que es appears to be grammaticalized in Spanish, although its use seems to receive a general negative assessment. It is usually categorized as an expletive or as a filler, because it is considered not to add any value to the discourse, especially when its use is too repeated. Two different objectives are pursued in this work. On the one hand, from a theoretical point of view, the pragmatic-discursive values ​​observed in the use of this marker are described: to the characteristic focus and theme functions, already expressed by some authors, others, observed thanks to data collected from two oral corpus of Spanish spoken in Granada, are added. On the other hand, from a descriptive point of view, we expose the social distribution of the uses of this marker, taking into account the factors of sex, age, level of education and origin (vernacular speakers from Granada versus immigrant speakers from Ecuador), we analyze its prestige and we address its possible not only dialectal, but also idiolectal nature.
Keywords: Granada; lo que es; migrants; pragmatics; discourse markers